Suppressive Effect of Tetrahydrocurcumin on Pseudomonas aeruginosa Lipopolysaccharide-Induced Inflammation by Suppressing JAK/STAT and Nrf2/HO-1 Pathways in Microglial Cells - Lin, Hui-Wen; Chen, Tzu-Chun; Yeh, Jui-Hsuan; Tsou, Shang-Chun; Wang, Inga; Shen, Ting-Jing; Chuang, Chen-Ju; Chang, Yuan-Yen (Oxidative medicine and cellular longevity, 2022)
Brain inflammation, a pathological feature of neurodegenerative disorders, exhibits elevated microglial activity and increased levels of inflammatory factors. The present study was aimed at assessing the anti-inflammatory response of tetrahydrocurcumin (THC), the primary hydrogenated metabolite of curcumin, which was applied to treat Pseudomonas aeruginosa (P.a.) lipopolysaccharide- (LPS-) stimulated BV2 microglial cells. THC reduced P.a. LPS–induced mortality and the production of inflammatory mediators IL-6, TNF-α, MIP-2, IP-10, and nitrite. A further investigation revealed that THC decreased these inflammatory cytokines synergistically with JAK/STAT signaling inhibitors. THC also increased Nrf2/HO-1 signaling transduction which inhibits iNOS/COX-2/pNFκB cascades. Additionally, the presence of the HO-1 inhibitor Snpp increased the levels of IP-10, IL-6, and nitrite while THC treatment reduced those inflammatory factors in P.a. LPS–stimulated BV2 cells. In summary, we demonstrated that THC exhibits anti-inflammatory activities in P.a. LPS-induced inflammation in brain microglial cells by inhibiting STAT1/3-dependent NF-κB activation and inducing Nrf2-mediated HO-1 expression.